The effect of eccentric strength training on heart rate and on its variability during isometric exercise in healthy older men - Takahashi, A. C M; Melo, R. C.; Quitério, R. J. [UNESP]; Silva, E.; Catai, A. M. (Springer Nature, 2009)
The purpose of this study was to investigate if chronic eccentric strength training (ST) affects heart rate (HR) and heart rate variability (HRV) during sub-maximal isometric voluntary contractions (SIVC). The training group (TG) (9 men, 62 ± 2) was submitted to ST (12 weeks, 2 days/week, 2 - 4 sets of 8-12 repetitions at 75-80% peak torque (PT). The control group (CG) (8 men, 64 ± 4) did not perform ST. The HR and the HRV (RMSSD index) were evaluated during SIVC of the knee extension (15, 30 and 40% of PT). ST increased the eccentric torque only in TG, but did not change the isometric PT and the duration of SIVC. During SIVC, the HR response pattern and the RMSSD index were similar for both groups in pre- and post-training evaluations. Although ST increased the eccentric torque in the TG, it did not generate changes in HR or HRV. © Springer-Verlag 2008.
Keywords: Autonomic nervous system; Heart rate; Heart rate variability; Isometric exercise; Strength training; adult; controlled study; eccentric strength training; eccentric torque; heart rate; heart rate variability; human; human experiment; isometric exercise; knee function; male; maximal voluntary contraction; muscle contraction; muscle isometric contraction; normal human; oxygen consumption; priority journal; submaximal isometric voluntary contraction; torque; training; voluntary movement; Adaptation, Biological; Aged; Autonomic Nervous System; Exercise Test; Heart Rate; Humans; Isometric Contraction; Male; Middle Aged; Muscle Fatigue; Muscle Strength; Physical Endurance; Resistance Training; Torque